A review on Haematococcus pluvialis bioprocess optimization of green and red Stage culture conditions for the production of natural astaxanthin - Oslan, Siti Nur Hazwani; Shoparwe, Noor Fazliani; Yusoff, Abdul Hafidz; Abdul Rahim, Ainihayati; Chang, Shen Chang; Tan, Joo Shun; Oslan, Siti Nurbaya; Arumugam, Kavithraashree; Ariff, Arbakariya; Sulaiman, Ahmad Ziad; Mohamed, Mohd Shamzi (Multidisciplinary Digital Publishing Institute, 2021)
As the most recognizable natural secondary carotenoid astaxanthin producer, the green microalga Haematococcus pluvialis cultivation is performed via a two-stage process. The first is dedicated to biomass accumulation under growth-favoring conditions (green stage), and the second stage is for astaxanthin evolution under various stress conditions (red stage). This mini-review discusses the further improvement made on astaxanthin production by providing an overview of recent works on H. pluvialis, including the valuable ideas for bioprocess optimization on cell growth, and the current stress-exerting strategies for astaxanthin pigment production. The effects of nutrient constituents, especially nitrogen and carbon sources, and illumination intensity are emphasized during the green stage. On the other hand, the significance of the nitrogen depletion strategy and other exogenous factors comprising salinity, illumination, and temperature are considered for the astaxanthin inducement during the red stage. In short, any factor that interferes with the cellular processes that limit the growth or photosynthesis in the green stage could trigger the encystment process and astaxanthin formation during the red stage. This review provides an insight regarding the parameters involved in bioprocess optimization for high-value astaxanthin biosynthesis from H. pluvialis.